Pregnancy lipid profile and different lipid patterns of gestational diabetes treated by diet itself - Cibickova, L; Langova, K; Schovanek, J; Macakova, D; Krystynik, O; Karasek, D (Physiological research, 2022)
The development of gestational diabetes mellitus (GDM) affects lipid metabolism during pregnancy. However, the magnitude of changes in lipid parameters is unclear. In addition, the patterns of these changes may vary based on the criteria selected for making the diagnosis of GDM. Thus, our aim was to compare the anthropometric and laboratory profiles of GDM-associated vs. GDM-free gestation with those of healthy non-pregnant women. We designed a cross-sectional study involving a group of females affected by GDM, a group of healthy pregnant controls and a group of healthy non-pregnant counterparts. GDM patients were divided into 3 subgroups according to the fulfilled diagnostic criteria, that is, those presenting with high fasting plasma glucose in the first trimester (subgroup 1), high fasting plasma glucose in the second trimester (subgroup 2) and high plasma glucose following oral glucose load in the second trimester (subgroup 3). The anthropometric and metabolic profiles of GDM subjects resembled the facets of metabolic syndrome (highest body mass index, waist circumference, C-peptide level, triglycerides) significantly more than the respective profiles of healthy non-pregnant women (p<0.0001). While total cholesterol (TC) (together with LDL-C and non-HDL-C) in pregnant women with GDM and without GDM did not differ, both groups had significantly higher levels of triglycerides (TG) than non-pregnant women (p<0.0001). Subgroup 1 had the highest fasting glucose level in the second trimester whereas subgroup 3 had the lowest fasting glucose level (p=0.019). Concentration of TG increased, being the lowest in subgroup 1 and the highest in subgroup 3 (p=0.006). Women with GDM had more pronounced features of metabolic syndrome than pregnant women without GDM. Both groups reached higher levels of TC (LDL-C, non-HDL-C) than non-pregnant controls and did not differ from each other. We found differences in TG and fasting glucose levels among different types of GDM.